The association of dietary patterns with latent tuberculosis infection among young adults: A case-control study in Shanghai - Yu Siyu; Li Shihong; Liu Yang; Jiang Yue; Cai Fengzhu; Xiao Shaotan; Hao Lipeng; He Gengsheng (Journal of Infection in Developing Countries)
Introduction: In developing and underdeveloped countries, undernutrition plays a major role in subverting the immune system, leading to an increase in TB infections; this study investigated the associations between dietary patterns and latent tuberculosis infection risk among young adults in Shanghai.